Characterizing free-living and particle-attached bacterial communities of a canyon river reservoir on the Yungui Plateau, China - Yang, Yang; Chen, Chen; Wang, Junyi; Xu, Tao (Frontiers in Microbiology, 2022)
Revealing the composition of free-living (FL) and particle-attached (PA) bacterial communities could provide insights into their distinct roles in biogeochemical processes and algal bloom dynamics. While there is still a lack of research about the difference and interactions between FL and PA communities, especially on the Yungui plateau with underestimated diversity. This study unveiled the structure of both FL and PA bacterial communities in a canyon reservoir (Wujiangdu) on the Yungui Plateau, southern China. Water samples were collected from surface water at nine sites in the reservoir. FL and PA bacterial community structures were identified by high-throughput 16S rRNA gene sequencing. We compared the structure and diversity of FL and PA bacteria and investigated their relationship with environmental factors. Results showed that there were different structures between FL and PA bacterial communities, and the dominant FL and PA phyla were affected by different environmental variables. Moreover, diversity of PA bacteria was greater than that of FL bacteria. Both groups exhibited distance decay patterns in this reservoir with varying correlations with geographic distances. FL fraction, however, exhibited a stronger correlation with environmental factors than the PA counterpart. Both FL and PA communities were phylogenetic clustering than expected according to the mean nearest taxon distance. This study provides fundamental information on FL and PA bacteria distribution and demonstrates how specific environmental factors affected these two bacterial fractions in canyon river reservoirs.